MiR-210 disturbs mitotic progression through regulating a group of mitosis-related genes - He, Jie (Oxford University Press, 2013)
MiR-210 is up-regulated in multiple cancer types but its function is disputable and further investigation is necessary. Using a bioinformatics approach, we identified the putative target genes of miR-210 in hypoxia-induced CNE cells from genome-wide scale. Two functional gene groups related to cell cycle and RNA processing were recognized as the major targets of miR-210. Here, we investigated the molecular mechanism and biological consequence of miR-210 in cell cycle regulation, particularly mitosis. Hypoxia-induced up-regulation of miR-210 was highly correlated with the down-regulation of a group of mitosis-related genes, including Plk1, Cdc25B, Cyclin F, Bub1B and Fam83D. MiR-210 suppressed the expression of these genes by directly targeting their 3′-UTRs. Over-expression of exogenous miR-210 disturbed mitotic progression and caused aberrant mitosis. Furthermore, miR-210 mimic with pharmacological doses reduced tumor formation in a mouse metastatic tumor model. Taken together, these results implicate that miR-210 disturbs mitosis through targeting multi-genes involved in mitotic progression, which may contribute to its inhibitory role on tumor formation.